Modeling and Simulation Study of Dry Ultrasonic Vibration-Assisted Grinding of Tool Steel With Single Alumina Abrasive Grit - Chaudhari A.; Sharma A.; Awale A.S.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
In the precision fabrication industries, ultrasonic vibration-assisted grinding is widely utilized for the finishing of "difficult-to-cut"materials due to its intermittent cutting mechanism and brittle-to-ductile mode machining. In this study, a two-dimensional finite element model (FEM) of single grit ultrasonic vibration-assisted dry grinding (UVADG) and conventional dry grinding (CDG) of AISI D2 steel has been developed, which taken into account the influence of longitudinal ultrasonic vibration on the workpiece with variable downfeed. The effects of ultrasonic vibration and downfeed on the chip formation mechanism, temperature field, grinding force, and equivalent stress and strain were evaluated by analytical and simulation methods. The results show that the formation of the grinding chips under UVADG is much shorter and straighter than CDG mode at all respective downfeed. The validation experiment compared the simulated and experimental grinding force in both grinding modes to verify the reliability of the FEM results. The validation results demonstrate that the FEM model can accurately describe the single grit UVADG and CDG grinding. At each downfeed, the CDG mode has generated a larger equivalent plastic strain than the UVADG mode, resulting in a higher thermomechanical load on the workpiece. According to the findings, UVADG mode has the least plastic damage on the ground surface, which may improve the surface integrity of the ground component. Copyright © 2022 by ASME.